2012
DOI: 10.1162/jocn_a_00111
|View full text |Cite
|
Sign up to set email alerts
|

Visual Processing of Contour Patterns under Conditions of Inattentional Blindness

Abstract: An inattentional blindness paradigm was adapted to measure ERPs elicited by visual contour patterns that were or were not consciously perceived. In the first phase of the experiment, subjects performed an attentionally demanding task while task-irrelevant line segments formed square-shaped patterns or random configurations. After the square patterns had been presented 240 times, subjects' awareness of these patterns was assessed. More than half of all subjects, when queried, failed to notice the square pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
247
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(273 citation statements)
references
References 87 publications
(91 reference statements)
20
247
6
Order By: Relevance
“…This finding is in line with studies that showed that perceptual grouping can occur under inattention (Kimchi & Razpurker-Apfeld, 2004;Moore & Egeth, 1997;Pitts, Martiń ez, andHillyard, 2011. Moore andEgeth (1997) asked participants to judge which of the two target lines are longer and found that the judgment was subject to conventional illusions (Ponzo Illusion and Muller-Lyer Illusion) produced by an above-threshold, but task-irrelevant, background organization; subjects were unable to report this background organization retrospectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in line with studies that showed that perceptual grouping can occur under inattention (Kimchi & Razpurker-Apfeld, 2004;Moore & Egeth, 1997;Pitts, Martiń ez, andHillyard, 2011. Moore andEgeth (1997) asked participants to judge which of the two target lines are longer and found that the judgment was subject to conventional illusions (Ponzo Illusion and Muller-Lyer Illusion) produced by an above-threshold, but task-irrelevant, background organization; subjects were unable to report this background organization retrospectively.…”
Section: Discussionsupporting
confidence: 92%
“…Moore andEgeth (1997) asked participants to judge which of the two target lines are longer and found that the judgment was subject to conventional illusions (Ponzo Illusion and Muller-Lyer Illusion) produced by an above-threshold, but task-irrelevant, background organization; subjects were unable to report this background organization retrospectively. More recently, Pitts et al (2011) isolated neural activity associated with specific stages of visual perception and awareness of display containing a contour or not, and found that the Nd1 component was elicited by contour patterns during inattentional blindness and was dissociated from components associated with awareness (which occur at a later time point in Nd2 component). In these studies, contour information is always presented above threshold but, because of diverted attention to the central task, the contour information is rendered in the ''inattention'' state and, thus, is not reported by participants.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, much of the work that has taken place has focused on activity in AC (particularly secondary AC), which is almost certainly a central hub of conscious auditory perception and auditory cognition in general [259]. However, what other aspects of brain activity might constitute the NCC A has not been examined to nearly the same extent as either their visual counterparts (but see [112,114,141,145,254,260] [261][262][263] (for reviews, see [10,30]). Motivated at least in part by the potential confound of overt perceptual reports [16,29,30], the picture that emerges from these studies is that traditional NCC markers from global-workspace theory (frontoparietal activity or the P3b, as measured via non-invasive neuroimaging) may instead reflect 'consequences' of conscious perception associated with task relevance and post-perceptual processing.…”
Section: Toward a Comprehensive Framework For Conscious Auditionmentioning
confidence: 99%
“…Along the lines of what we have previously argued [2][3][4] , the authors emphasize the role of sensory areas as prime candidates for neural correlates of consciousness (NCC). However, although visual conscious experience certainly appears to be related to activity in the posterior cortical regions, this is probably not the case for conscious experiences within other sensory domains where perceptual processing does not take place in the posterior cortex -the gustatory cortex, for instance, is located partly in the frontal lobe.…”
mentioning
confidence: 92%